Models and forms of a secular state and religious relations in modern Western countries - Majiev , G. Zh. (BULLETIN of the L.N. Gumilyov Eurasian National University. Historical sciences. Philosophy. Religion Series, 2020)
In this article, the author analyzed the forms of interaction of religious associations and the state in Western countries. Currently, there is no clear general model in the world practice related to the relationship between the state and religion, especially with the principles of secularism, and a large number of conclusions about secularity studied to date show that researchers need even more research in this direction. In particular, this is a topical issue for countries oriented towards the secularity model of Western countries in preventing future problems and positively implementing secularism principles. Within the framework of the topic, special attention was paid to the countries of Europe, Italy, France, Germany, Great Britain, studied by a comparatively analytical method of similarities and differences in their positions in state-confessional relations. As a result, several features and differences between these countries in this direction were established.